Artificial weathering of heat-treated pines from the Iberian peninsula - Esteves, Bruno M. (2021)
Samples from the two most common pines grown in Portugal (Pinus pinaster Ait) and Spain (Pinus radiata, D. Don) were heat-treated in industrial facilities in accordance with ThermoWood ® class D. For both species, the variation in surface properties, of untreated and heat-treated wood after artificial weathering from 75 to 750 h, is presented. The analysis included the determination of color, roughness, gloss, and wettability before exposure and after each artificial weathering period. Untreated woods became darker faster, while in heat-treated woods, lightness remained approximately constant until 750 h of artificial weathering. Both untreated and heat-treated wood became more reddish in the beginning of the weathering process, turning greener for longer exposure times. Untreated woods became yellower in the beginning, turning into blueish tones later. Heat-treated wood turned slightly yellower until 750 h of weathering. Gloss decreased for untreated wood with no significant changes in heat-treated wood. Despite the changes, the gloss of both untreated and heat-treated wood converged to similar values. Roughness increased for both untreated and heat-treated woods. Artificial weathering increased the wettability of heat-treated wood.